2009
DOI: 10.1097/mao.0b013e3181c2a084
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of High-Resolution CT Scan in Diagnosis of Otosclerosis

Abstract: In our series, the sensitivity of HRCT scan to otosclerosis was 95.1%. Hypodense otosclerotic foci were mostly localized at the anterior part of footplate. Negative or doubtful cases were associated with the highest incidence of stapes footplate complications. Foci involving otic capsule, internal auditory canal, or round window led to a significantly higher risk of sensorineural hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
95
2
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(116 citation statements)
references
References 17 publications
11
95
2
5
Order By: Relevance
“…Point-biserial correlation coefficients were computed. In the sABG group, a small positive correlation was observed between poor audiometric outcome and negative preoperative CT scan, which is in line with the findings of Lagleyre et al [2009]. Note, however, that this correlation was not statistically significant, probably because of the presence of small samples of patients.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Point-biserial correlation coefficients were computed. In the sABG group, a small positive correlation was observed between poor audiometric outcome and negative preoperative CT scan, which is in line with the findings of Lagleyre et al [2009]. Note, however, that this correlation was not statistically significant, probably because of the presence of small samples of patients.…”
Section: Resultssupporting
confidence: 84%
“…The correlation (even if it is weak because of the small sample) in our study between poor audiometric results and negative preoperative CT in the sABG group is also a reason to make preoperative CT scans before surgery. In the same way Lagleyre et al [2009] demonstrated a high sensitivity of high-resolution CT scan for otosclerosis (95.1%) and a relationship between negative or doubtful CT scan, which were associated with the highest incidence of stapes footplate complications. Although many centers (as ours) still do not do it systematically, it seems that a preoperative CT scan is mandatory before all otosclerotic surgery.…”
Section: Audiometric Results After Stapedotomymentioning
confidence: 61%
“…Oblique axial plane could enhance the CT analysis of the stapes and provide useful biometric landmarks in pathologic conditions (5). High-resolution computed tomography scan (HRCT scan) is good for the precise anatomical details in the middle ear (10). we established the diagnosis of otosclerosis with avascular necrosis of stapes crura during surgery work and with histopathological finding of stapes suprastructure.…”
Section: Discussionmentioning
confidence: 99%
“…The disease sometimes involves only the cochlear endosteum and can manifest with sensorineural hearing loss (SNHL). This condition is called cochlear otosclerosis and accounts for 1% of patients with otosclerosis [4] . Treatment options for otosclerosis include medical treatment, hearing aids, and surgical management.…”
Section: Introductionmentioning
confidence: 99%